The Moderating Role of Digital Culture in the Relationship between Physical Ergonomics and Organizational Culture in SMI - Mohammad Fajar Nurwildani; Hari Purnomo; Elisa Kusrini; Hartomo Soewardi (Advance Sustainable Science Engineering and Technology, 2026)
This study investigates the moderating role of digital culture in the relationship between physical ergonomics, organizational culture, and the performance of Small and Medium Industries (SMI). Using survey data from 123 manufacturing SME employees in Tegal, Indonesia, the analysis employed Structural Equation Modeling (SEM-AMOS). The findings reveal that digital culture significantly moderates the relationship between physical ergonomics and organizational culture (β = 0.083; CR = 12.126; p < 0.001). However, physical ergonomics demonstrated an unexpected negative effect (β = –1.031; CR = –5.958; p < 0.001). In addition, organizational culture was found to have no significant influence on performance (β = 0.113; CR = 1.038; p = 0.299). These counterintuitive results highlight digital culture as a key moderator that strengthens the adaptive role of ergonomics. The study contributes by demonstrating the complex interplay between ergonomics, organizational culture, and digitalization, offering practical insights for SME managers to integrate ergonomic practices with digital initiatives to enhance competitiveness.